2019
DOI: 10.1002/cne.24709
|View full text |Cite
|
Sign up to set email alerts
|

Unusual topographic specializations of retinal ganglion cell density and spatial resolution in a cliff‐dwelling artiodactyl, the Nubian ibex (Capra nubiana)

Abstract: The Nubian ibex (Capra nubiana) occurs in information‐rich visual habitats including the edges of cliffs and escarpments. In addition to needing enhanced spatial resolution to find food and detect predators, enhanced visual sampling of the lower visual field would be advantageous for the control of locomotion in such precarious terrains. Using retinal wholemounts and stereology, we sought to measure how the ganglion cell density varies across the retina of the Nubian ibex to reveal which portions of its surrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The dorsotemporal extension forms a dorsal arch of ganglion cells increase Some authors reported that this specialization is closely related with demands required by the inferior visual field such as spotting predators, orientation during foraging or ambulation [32]. It was also found in other artiodactyl living in mountains and valleys [42], which points to a shared ecological niche.…”
Section: Plos Onementioning
confidence: 94%
See 2 more Smart Citations
“…The dorsotemporal extension forms a dorsal arch of ganglion cells increase Some authors reported that this specialization is closely related with demands required by the inferior visual field such as spotting predators, orientation during foraging or ambulation [32]. It was also found in other artiodactyl living in mountains and valleys [42], which points to a shared ecological niche.…”
Section: Plos Onementioning
confidence: 94%
“…We used morphological criteria to differentiate ganglion cells from neuroglial cells and displaced amacrine cells according to Hughes [41] The same criteria was used in other studies for artiodactyls species [32,42,43] and other species [17,40,44]. Briefly, ganglion cells have a large soma with an oval pale nucleus and a prominent nucleolus with abundant Nissl substance visible in the cytoplasm.…”
Section: Gross Anatomy Retinal Area and Identification Of Ganglion Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, medium-and large-sized cervid species (Table 1) might not have sufficient visual resolution for nearby ground objects due to an increased ground-to-eye distance [31]. In both the domestic sheep (Ovis aries) and the Nubian ibex (Capra nubiana), the dorsotemporal extension of their M-cone topography corresponds with an increase in ganglion cell density at the temporal region of the visual streak and the dorsotemporal region [78,79]. Increased ganglion cell and M-cone density near the temporal and dorsotemporal regions of midand large-size cervids might improve the visual resolution in the frontal and lower visual fields.…”
Section: Predator Detection and Avoidancementioning
confidence: 99%
“…Retinal ganglion cell (RGC) density maps have been used to estimate visual spatial resolution of a wide range of terrestrial vertebrates including birds (e.g., Wathey and Pettigrew, 1989;Hart, 2002;Coimbra et al, 2012;Mitkus et al, 2014;Lisney et al, 2020), reptiles (e.g., Hart et al, 2012;Hauzman et al, 2014), and mammals (e.g., Coimbra et al, 2013;Coimbra et al, 2017a;Coimbra et al, 2019). Spatial resolution has been estimated from RGC density in more than 25 bat species including 12 pteropodids (online Suppl.…”
Section: Introductionmentioning
confidence: 99%